The Effect of Service Quality and Service Innovation on Customer Satisfaction at PT PLN (Persero) ULP Teluk Betung - Pradita, Selvy; Barusman, Muhammad Yusuf Sulfarano (Formosa Journal of Multidisciplinary Research, 2024)
This research uses quantitative methods, involving 100 respondents as samples. During this process, the instruments in the study were tested for validity and reliability. Followed by a classic assumption test consisting of normality test and multicollinearity test. Furthermore, hypothesis testing includes multiple linear regression analysis, coefficient of determination (R2 ), t test and f test. The purpose of this study was to determine whether service quality and service innovation affect customer satisfaction at PT PLN (Persero) ULP Teluk Betung. In this study, Service Quality affects Customer Satisfaction. This shows that the hypothesis is accepted. The value of Service Quality t count is 4.246> from t table 1.984. The results showed that Service Quality significantly affected Customer Satisfaction, Service Quality was rated positively in multiple regression analysis. The results of the study Service Innovation has a positive and significant effect on Customer Satisfaction, meaning that the hypothesis is accepted. The t test results show that the t value of Service Innovation is greater than the t table (7.256> 984). In multiple regression analysis, Service Innovation has a positive value on Customer Satisfaction. PLN is a state-claimed business that is delegated as a provider of electricity. Therefore, it needs a lot of innovation to attract new customers and service quality must be the main focus because it can create customer satisfaction and will affect customer loyalty.